Teacher Experiences in Teaching Reading Comprehension: A Qualitative Study in English Classes at UPT SMP Negeri 10 Medan - Ginting, Uni Tripina; Br Sembiring, Yenita; Lumbanbatu, Ira Maria Fran (Indonesian Journal of ELT and Applied Linguistics, 2024)
This study aims to analyze teachers' experiences in teaching reading comprehension in English classes at UPT SMP Negeri 10 Medan. This research employs a qualitative approach using interviews, observations, and a Likert-scale-based questionnaire to explore various aspects of reading comprehension instruction. The main focus of this study includes the strategies used by teachers, the effectiveness of learning media, student engagement in interactive activities, and the challenges faced in understanding reading texts. The findings indicate that teachers employ various strategies such as skimming and scanning, group discussions, and role-playing to enhance students' reading comprehension. The use of learning media such as videos, images, and mind mapping has been proven to help students better understand texts. Group discussions are also an effective method for improving reading skills, particularly in fostering a deeper understanding of texts. However, this study also reveals several challenges, including limited vocabulary, low reading interest, and difficulties in comprehending complex text structures. The implications of this study highlight the importance of utilizing diverse and innovative teaching methods to cater to students' needs. Additionally, vocabulary enrichment and the selection of reading materials relevant to students' lives can enhance their motivation and comprehension of English texts.